Tunability of optical constants of Se-Ge-Ag thin films based on change in resistivity with temperature for solar cells. Issue 15 (1st August 2021) - Ahmed, Moustafa; Al-Hadeethi, Yas M.; Kutbee, Arwa T.; Shaaban, Essam R.
Abstract: Thin films of semiconductor Se80 Ge20-x Agx (x = 0, 3, 6, 9, 12 and 15 at.%) were deposited by the thermal evaporation technology. Through optical and electrical characterization, the influence of the Ag ratio on the photoelectric parameters of Se–Ge thin film was studied. The X-ray diffraction pattern showed the amorphous nature of the deposited films as well as the polycrystalline state when the films were annealed at the maximum crystallization temperature (415 K), which was determined by the first derivative of the resistivity curve with respect to temperature. The crystallization kinetics of the film was extracted from the electrical analysis by measuring the change in resistivity with temperature. The electrical results of the thin film showed three regions; namely, amorphous, extended (crystalline) and hopping. In the extended and hopping states, the activation energy and pre-exponential factors were calculated. The optical constants, extinction coefficient and refractive index were calculated using the transmittance and reflectance of the grown Se80 Ge20-x Agx films. The energy gaps of the films were estimated in the strong absorption regions. The changes in the bandgap energy of the film by thermal annealing can help to produce materials with acceptable band gaps for use as absorber layers in solar cell applications. Also, the results provide microscopic insights and studies on the structure, electr-othermal and optical properties of Ag metal-doped GeSe as a back contact of solar cells.